Development of subjectivity of future teachers in the course of professional training - Vera S. Gorynina; Il’dar M. Yusupov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The values of public life in the twenty first century have changed dramatically. For successful socialization, specialists need: critical thinking, readiness for changes, reasonableness of their dispositions, conscious decision making, and active management of the situation. Psychologists have designated this set of personal qualities as subjectivity. At all times, it has not lost its professional significance for teachers, and today compliance with the challenges of the era is becoming relevant for them. Subjectivity of future teachers trained in colleges and universities should be considered as an adaptive quality of personality that requires creativity of mind and behavior. Debates about the psychological content of subjectivity, its types, and determinants of formation and change have not clearly defined it as a theoretical category of scientific psychology. The purpose of the conducted empirical research is to identify the types of subjectivity of future teachers in educational activities. We studied the development of subjectivity of future teachers in the learning process. It was assumed that the dominant type of consciousness of the student determines the configuration of its subjectivity, which can be changed in the course of training. Subjectivity is presented as a psychological construct integrally describing the ability of a personality to voluntarily change oneself and the surrounding reality. The criteria distinguishing it from consciousness are value-meaning orientation and self-regulation, which are revealed in transformational activity. Subjectivity was researched in 314 students of pedagogical universities and technical schools during four years of their studies. The type of prevailing consciousness was diagnosed by the indicators «active» and «contemplative» and communicativeness - by the indicators «communicability» and «reflectivity». The results are presented as graphic profiles of subjectivity, which are classified into four types according to the dominating indicator: «philosopher», «organizer», «facilitator» and «teacher»; the types were further described. The psychological support of the students was performed with a view of increasing their subjectivity. This was achieved via trainings promoting consciousness, social activity, self-concept, and aspirations. The final diagnostics of the future teachers showed subjectivity increase by the above indicators: in the group of technical school students - from 17 to 32%, in the group of full-time university students - from 16 to 22 %, in the group of university students by correspondence - from 12 to 23 %.